1989
DOI: 10.1007/bf00392811
|View full text |Cite
|
Sign up to set email alerts
|

A stable blue-light-derived signal modulates ultraviolet-light-induced activation of the chalcone-synthase gene in cultured parsley cells

Abstract: Run-off transcription assays were used to demonstrate that both the ultraviolet (UV)-B and blue-light receptors control transcription rates for chalcone-synthase mRNA in the course of light-induced flavonoid synthesis in parsley (Petroselinum crispum Miller (A.W. Hill)) cell-suspension cultures. Blue and red light alone, presumably acting via a blue-light receptor and active phytochrome (far-red absorbing form) respectively, can induce accumulation of chalcone-synthase mRNA. The extent of the response is howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 27 publications
12
70
1
Order By: Relevance
“…Irradiation resulted in a greater than 100-fold induction in phenylpropanoid synthesis. This is consistent with published studies where BL initiates phenylpropanoid production (Long and Jenkins, 1998;Noh and Spalding, 1998), and preirradiation of parsley (Petroselinum crispum) cells in culture prior to UV treatment reduces a lag period for expression of Phe derivatives (Bruns et al, 1986;Ohl et al, 1989). Lag elimination is often indicative of precursor synthesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Irradiation resulted in a greater than 100-fold induction in phenylpropanoid synthesis. This is consistent with published studies where BL initiates phenylpropanoid production (Long and Jenkins, 1998;Noh and Spalding, 1998), and preirradiation of parsley (Petroselinum crispum) cells in culture prior to UV treatment reduces a lag period for expression of Phe derivatives (Bruns et al, 1986;Ohl et al, 1989). Lag elimination is often indicative of precursor synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…In higher plants, blue light (BL) is known to affect the phenylpropanoid pathway, which initiates with Phe, and for which Phe can be a limiting component (Bruns et al, 1986;Ohl et al, 1989;Long and Jenkins, 1998;Noh and Spalding, 1998). At least three photoreceptor systems are known to act in BL-mediated phenomena: PHOTOTROPIN, CRYPTOCHROME, and PHYTOCHROME (Ahmad, 1999;Briggs and Huala, 1999;Casal, 2000;Lin, 2000;Chen et al, 2004).…”
mentioning
confidence: 99%
“…Because some UV-B responses, e.g. chalcone synthase (CHS) expression, can be modulated by blue or red light, there is evidence that a complex web exists between phytochrome-, cryptochrome-, and UV-B-signaling chains in cell cultures (Ohl et al, 1989) and plants (Boccalandro et al, 2001;Wade et al, 2001).…”
Section: Uv-b Signal Perceptionmentioning
confidence: 99%
“…Synchronous transcriptome changes of flavonoid biosynthetic genes have been first described in parsley cell cultures. Early components of this metabolic pathway are transcriptionally activated in a timely coordinated manner within a few hours (Hahlbrock and Scheel, 1989;Ohl et al, 1989;Loyall et al, 2000). Several light-responsive promoters of this pathway were analyzed (Logemann and Hahlbrock, 2002) and a number of conserved cisacting elements were described that confer light responsiveness.…”
Section: Transcriptome Changes Triggered By Uv-b Radiationmentioning
confidence: 99%
“…The parsley suspension culture and the protoplasts and evacuolated protoplasts derived from this culture have been intensively analyzed for the light regulation of different genes, including those encoding CHS and phytochrome. Detailed studies have shown that all known photoreceptors are physiologically active in this system (Ohl et al, 1989;Frohnmeyer et al, 1992;Merkle et al, 1994;Rocholl et al, 1994; C. Poppe, E. Ehmann, H. Frohnmeyer, and E. Schafer, manuscript submitted). We have recently established a silicon oil gradient centrifugation technique to isolate a pure and highly concentrated plasma membranecontaining cytosolic fraction from parsley protoplasts that have first been evacuolated by Percoll gradient centrifugation .…”
Section: Introductionmentioning
confidence: 97%